From Print to Digital, from Document to Data: Digitalisation at the Publications Office of the European Union - Schafer, Valérie (OPEN INFORMATION SCIENCE, 2020)
Since the 1970s, the Publications Office of the European Union, the official publisher of all the institutions and bodies of the EU, has had to adapt to a fast-changing situation as the number of EU Member States has grown and the number and nature of publications has evolved (including publishing public tenders of EU institutions and Member States in 1978 through a supplement to the and handling CELEX, an interinstitutional and multilingual automated documentation system for community law, in 1992). These changes occurred over several ages of computing. The computerisation of the Publications Office was primarily a response to the need for rationalisation and productivity, but the aim was also to gradually adapt to new types of document publication and consultation. These different stages of digitalisation required the constant transfer of information to a multitude of media. Supports, such as punched cards, optical discs and CD-ROMs, had varying life expectancies and are all evidence of attempts to digitise information before the Web. This evolution not only illustrates the need to constantly harmonise a large amount of information, it also highlights some continuities. It affects the management of information systems but also meets regularly updated standardisation, interoperability and sustainability needs within a complex ecosystem.